Alter-Globalization: Becoming Actors in the Global Age - Malay Jr., Armando (Kasarinlan: Philippine Journal of Third World Studies, 2012)
Review of Alter-Globalization: Becoming Actors in the Global Age (2010) by Geoffrey Pleyers (Cambridge, UK, and Malden, MA, USA: Polity Press).